Newcomer Socialization research: The Importance and Application of Multilevel Theory and Communication. Issue 1 (1st January 2015) - Manata, Brian; Miller, Vernon D.; DeAngelis, Briana N.; Esther Paik, Jihyun
Abstract : Although multiple conceptualizations and measures of newcomer socialization have been offered, most approaches to measuring socialization efforts (a) confound distinctions between multilevel influences and (b) overlook critical communicative aspects (i.e., who-says-what-to-whom-and-how). Advocating for a shift in theory and measurement, this paper reviews three popular approaches in the socialization corpus (i.e., contextual, content, and memorable messages) and then critiques their inattention to the multilevel and communicative nature of socialization processes. This paper concludes with recommendations for future research on the dynamics of newcomer socialization, especially as they occur across multiple levels of analysis.